2018
DOI: 10.3390/foods7090146
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid-Rich Extract of Actinidia macrosperma (A Wild Kiwifruit) Inhibits Angiotensin-Converting Enzyme In Vitro

Abstract: Increasing interest in flavonoids in kiwifruit is due to the health-promoting properties of these bioactives. Inhibition of the angiotensin-converting enzyme (ACE) is one of the main therapeutic targets in controlling hypertension. The present study investigated the ACE inhibitory activity of flavonoid-rich extracts obtained from different kiwifruit genotypes. The flavonoid-rich extracts were prepared from fruits of Actinidia macrosperma, Actinidia deliciosa cv Hayward (Green kiwifruit), and Actinidia chinensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Several biological activities have already been reported for kiwifruit (Actinidia macrosperma) cultivars, such as antioxidant, anticancer, anti-inflammatory, and antimicrobial activities. This Special Issue contains the first report on a study supporting the potential anti-hypertensive activities of kiwifruits [1]. The results of this study clearly indicate that the flavonoid-rich extract from A. macrosperma shows potential as a food or nutraceutical source of anti-hypertensive agents.…”
mentioning
confidence: 61%
“…Several biological activities have already been reported for kiwifruit (Actinidia macrosperma) cultivars, such as antioxidant, anticancer, anti-inflammatory, and antimicrobial activities. This Special Issue contains the first report on a study supporting the potential anti-hypertensive activities of kiwifruits [1]. The results of this study clearly indicate that the flavonoid-rich extract from A. macrosperma shows potential as a food or nutraceutical source of anti-hypertensive agents.…”
mentioning
confidence: 61%
“… 39 In vitro studies have demonstrated that flavonoid-rich foods are capable of inhibiting ACE activity. 40 42 Also, an acute hypertensive rat model supports the antihypertensive potential of quercetin through reduced plasma ACE activity. 43 In contrast, ACE inhibition by flavonoids has not been observed in other human and animal studies.…”
Section: Discussionmentioning
confidence: 83%
“…UPLC-MS/MS showed that polyphenols (231.32 µg/g DW) in the extract are mainly flavonols, flavanols, and phenolic acids. Specifically, quercetin-3-O-galactoside (205.19 µg/g DW), quercetin-3-O-glucoside (0.45 µg/g DW), quercetin-3-O-rhamnoside (0.61 µg/g DW), quercetin-3-O-rutinoside (0.29 µg/g DW), epicatechin (5.15 µg/g DW), catechin (0.75 µg/g DW), epigallocatechin (0.61 µg/g DW), phloridzin (2.03 µg/g DW), and isoferulic acid (15.12 µg/g DW) are major compounds in the extract (Hettihewa et al, 2018). These compounds could be responsible for the observed in vitro ACE inhibitory activity of Hort 16A fruit, though the active compounds identifying and in vivo animal studies remain to be investigated and conducted.…”
Section: Chemical Compositionmentioning
confidence: 99%